Decoding Black Feminist Hashtags as Becoming. - Conley, Tara L. (Black Scholar, 2017)
The article talks about the hashtag #YouOkSis introduced by two black women for women of color to share intimate stories of experiencing or witnessing dehumanization by way of sexual violence in public view. Topics discussed include gendered and racialized specificity in theories of social organization and the aim of this article being to capture the ways in which black women's encounters and bodies have been entangled among sociopolitical processes of domination and authority.